Development and Validation of a Nomogram for Predicting Generalization in Patients With Ocular Myasthenia Gravis - Ruan, Zhe; Sun, Chao; Lang, Yanlin; Gao, Feng; Guo, Rongjing; Xu, Quan; Yu, Liping; Wu, Songdi; Lei, Tao; Liu, Yu; Zhang, Min; Li, Huanhuan; et al. (Frontiers in Immunology, 2022)
Background: This study aims to develop and validate a nomogram for predicting 1- and 2-year generalization probabilities in patients with ocular myasthenia gravis (OMG). Methods: In total, 501 eligible patients with OMG treated at seven tertiary hospitals in China between January 2015 and May 2019 were included. The primary outcome measure was disease generalization. A nomogram for predicting 1- and 2-year generalization probabilities was constructed using a stepwise Cox regression model. Nomogram performance was quantified using C-indexes and calibration curves. Two-year cumulative generalization rates were analyzed using the KaplanMeier method for distinct nomogram-stratified risk groups. The clinical usefulness of the nomogram was evaluated using decision curve analysis (DCA). Results: The eligible patients were randomly divided into a development cohort (n=351, 70%) and a validation cohort (n=150, 30%). The final model included five variables: sex, onset age, repetitive nerve stimulation findings, acetylcholine receptor antibody, and thymic status. The model demonstrated good discrimination (C-indexes of 0.733 and 0.788 in the development and validation cohorts, respectively) and calibration, with good agreement between actual and nomogram-estimated generalization probabilities. KaplanMeier curves revealed significantly higher 2-year cumulative generalization rates in the high-risk group than in the low-risk group. DCA revealed a higher net benefit of nomogram-assisted decisions compared to treatment of all patients or none. Conclusion: The nomogram model accurately predicted 1- and 2-year generalization probabilities in patients with OMG and stratified patients into distinct risk groups. The nomogram may facilitate patient selection for initiation of immunotherapy and enrolment in clinical trials of risk-modifying treatments.